Analysis of Student and Faculty Perceptions of Textbook Costs in Higher Education - Michael Troy Martin; Olga Maria Belikov; John Hilton III; David Wiley; Lane Fischer (Open Praxis, 2017)
The cost of textbooks has continued to impact students in higher education. Students have reported that they make decisions on which courses to take based on the specific cost of textbooks. Faculty have reported willingness to use open textbooks to help ease the burden on students but are unsure where to find viable options. We examined the responses of 676 students and 573 faculty from a large private university (Brigham Young University, Provo, Utah) to understand the real impact of textbooks costs to students and how they are dealing with this ongoing problem. We found that 66% of students at this institution have not purchased a textbook due to cost. We also discovered that 91% of faculty at this institution would be willing to use OER alternatives and that 53% of them would welcome assistance identifying and adapting materials for their course.